Assessing the Goals of Art Education in the Content of the Eighth Grade Culture and Art Book (Case Study: The Views of Specialized Teachers of Culture and Art in Shiraz in the Academic Year of 2018-2019) - Maryam Fathi; Ashkan Rahmani (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
In the present study, the goals of art education in the content of the eighth-grade culture and art book have been studied. The goals of art education include art production, aesthetics, art criticism and art history. The use of these goals and their types are specified in different parts of the book. The main question that the authors seek to answer is; what are the goals of the art education used in the content of the eighth-grade culture and art book? This research is a descriptive and survey type that has been done with a questionnaire using a simple random sampling method among 54 art teachers in Shiraz. The findings have been analyzed quantitatively. The findings of this study show that the goals of art education in the total content of the book are moderate and the design chapter has the most application compared to other chapters of the book. "History of art" as one of the goals of art education in the design chapter and the purpose of "art production" in the chapter of illustration, photography and calligraphy have been most used. According to art experts, the most important goal of art education is to cultivate creativity.